2019
DOI: 10.1097/coc.0000000000000592
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-related Proteins as a Prognostic Factor of Patients With Colorectal Cancer

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…e loss of autophagy-related protein Beclin-1 is associated with poor prognosis in CRC [22]. On the other hand, Koustas et al [23] showed that the overexpression of Beclin-1 indicated a poor prognosis in CRC patients receiving chemotherapy. e high expression of LC-3 is positively correlated with the long-term survival of patients with CRC, which could be used as a biomarker for its prognosis [24].…”
Section: Introductionmentioning
confidence: 99%
“…e loss of autophagy-related protein Beclin-1 is associated with poor prognosis in CRC [22]. On the other hand, Koustas et al [23] showed that the overexpression of Beclin-1 indicated a poor prognosis in CRC patients receiving chemotherapy. e high expression of LC-3 is positively correlated with the long-term survival of patients with CRC, which could be used as a biomarker for its prognosis [24].…”
Section: Introductionmentioning
confidence: 99%
“…The role of autophagy in tumoral response is crucial in colorectal cancer. It has been shown in human colorectal tumors that surexpression of Beclin-1 was a poor prognosis factor with a lower efficacity of chemotherapy (37). Oxaliplatin inhibits autophagy in colorectal cancer with microsatellite stability (38).…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 , 16 ] Meanwhile, autophagy-based prognostic markers for CRC have also been reported. [ 17 , 18 ] However, most studies only focus on autophagy without considering the heterogeneity of CRC. To our knowledge, no research has been done for risk stratification by integrating the autophagy system and the mesenchymal modalities of CMS4 in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…We pooled and analyzed 6 public cohorts containing 1428 CRC patients to develop and validate an autophagy gene-based prognostic signature for CRC (APSCRC). Although autophagy prognostic markers for CRC have already been mentioned before, [ 17 , 18 ] risk assessment incorporating molecular subtypes has not been investigated. Our signature incorporates the autophagy system and tumor heterogeneity and would be useful for selecting patients with CRC to give more precise treatment.…”
Section: Introductionmentioning
confidence: 99%